PUBLIC SERVICE PERFORMANCE IN THE SIBOLGA SAMBAS DISTRICT OF NORTH SUMATRA PROVINCE - Ardhiansa Panggabean; Maksum Syahri Lubis; Beby Masitho Batubara (International Journal of Cultural and Social Science, 2026)
This study aims to analyze employee performance in public service delivery at the Sibolga Sambas Subdistrict Office, North Sumatra Province, and to identify the inhibiting factors affecting such performance. Public service performance is a key indicator in achieving good governance; therefore, employee performance plays a crucial role in determining the quality of services received by the community. This research employs a qualitative descriptive approach. Data were collected through observation, interviews, and documentation involving key informants, including the subdistrict secretary, staff members, and community members as service users. The analysis of public service performance refers to the service quality dimensions proposed by Parasuraman, Zeithaml, and Berry, namely tangibles, reliability, responsiveness, and assurance. The findings indicate that employee performance in public service delivery at the Sibolga Sambas Subdistrict Office is generally categorized as fairly good, particularly in terms of responsiveness and assurance. However, several obstacles remain in the aspects of reliability and tangibles, such as limited facilities and infrastructure, as well as suboptimal service systems. The inhibiting factors include limited operational budgets, uneven workload distribution, lack of capacity-building training, and an evaluation system that has not been fully optimized. Therefore, improvement efforts are required through enhancing employee competence, strengthening performance management, and providing adequate facilities and infrastructure to sustainably improve public service quality.